A rare case of primary pleural synovial sarcoma - Marić, Nebojša; Nikolić, Aleksandar; Cvijanović, Vlado; Ristanović, Aleksandar; Vešović, Nataša; Stojković, Dejan; Kostovski, Vanja; Djenić, Ljubinko; Čičić, Stevan (Vojnosanitetski pregled, 2021)
Introduction. Pleural synovial sarcoma (SS) is a rare type of mesenchymal tumor, that can easily be misdiagnosed. Case report. We presented a case of primary monophasic SS of the pleura in a middle-aged woman who initially presented with dyspnoea and a large pleural effusion. Computed tomography (CT) scans showed a large, well-demarcated right lung tumor mass. After a blind closed biopsy of the pleura, the tumor was misdiagnosed as adenocarcinoma and treated with chemotherapy but without response. The correct diagnosis was established after surgery and histological and immunohistochemical analyses. The diagnosis was fulfilled with cytogenetic analysis showing the typical translocation t (X,18). The tumor was completely extirpated during surgery. CT of the chest done four, and positron emission tomography done six months after surgery showed encapsulated reactive pleural effusion without tumor rest or relapse. In contrast, a CT scan done nine months after surgery showed an extrapulmonary soft-tissue mass in contact with the lower right lobe highly suspicious of tumor relapse. Surgery was performed, and the described mass was extirpated, but histological analysis showed no presence of malignant tissue. CT scan performed three months later showed no signs of the disease relapse. Conclusion. Considering that pleural SS can easily be misdiagnosed, immunohistochemical as well as cytogenetic analysis should always be performed in order to reach the proper diagnosis.
Keywords: cytogenetics; diagnosis; immunohistochemistry; pleural neoplasms; sarcoma, synovial; thoracic surgical procedures; treatment outcome